The risk assessment of inorganic and organic pollutant levels in an urban area affected by intensive industry - Hanousková, Barbora; Száková, Jiřina; Rychlíková, Eva; Najmanová, Jana; Košnář, Zdeněk; Tlustoš, Pavel (Environmental monitoring and assessment, 2021)
The city of Litvínov (North Bohemia, Czech Republic) is seriously affected by coal mining, coal processing, and intensive industrial activities. Within the urban area, the potential environmental hazard of risk elements (in soil and vegetation) and polycyclic aromatic hydrocarbons (PAHs, in soils) was estimated using selected environmental and human health hazard indices. In total, 24 sites were sampled, including the city center, residential areas, industrialized zone, and areas close to operating and/or abandoned coal mines. The results showed elevated values of As, Cd, Cu, Ni, Pb, and Zn in soils (the maximum levels of individual pollution indices varied between 3 and 5 for As, Pb, and Zn); the risk assessment code (RAC) values indicated high bioaccessibility of Cd and Zn. The high mobility of Cd was confirmed by their bioaccumulation factors (BAF) in the aboveground biomass of Taraxacum sect. Ruderalia and Polygonum aviculare, reaching up to 1.9 and 2.9, respectively. The Cd content in plants presents a substantial health hazard for herbivores such as Oryctolagus cuniculus living within the urban area. The PAH levels in the soils also showed elevated values; the contents of benzo(a)pyrene exceeded more than 2-fold the indicative values for potential health risk for biota, especially near the abandoned coal mines. The incremental lifetime cancer risks (ILCR) for ingestion of the contaminated soil showed only low or negligible cancerogenic risk, varying between 6.7 × 10-7 and 1.6 × 10-5 for children, and between 9.9 × 10-7 and 2.7 × 10-6 for adults. However, the potential health impact of the inhalation of the contaminated particulate matter should be included in the further research. Although the contamination level in the investigated area does not represent an imminent environmental and health risk, the potential remediation measures should be considered in the future.
Keywords: Environmental Pollutants; monitorování životního prostředí; látky znečišťující životní prostředí; látky znečišťující půdu; Cities; Risk elements; Česká republika; Risk Assessment; Environmental Monitoring; Urban area; Polycyclic aromatic hydrocarbons; Adult; polycyklické aromatické uhlovodíky; Czech Republic; dítě; Plants; Child; Soil Pollutants; hodnocení rizik; zvířata; Humans; Soil; králíci; Risk assessment; Polycyclic Aromatic Hydrocarbons; Rabbits; velkoměsta; dospělí; půda; lidé; Animals